THE INFLUENCE OF ORGANIZATION CAPABILITIES AND ENTREPRENEURSHIP TO COMPETITIVE ADVANTAGE IN GOODNESS OF TASTE AND THE IMPLICATION TO BUSINESS PERFORMANCE IN SME RESTAURANTS, SEMARANG - Bungara, Artsswinda Ayu (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2018)
This research was aimed to analyze the influence of capabilities organization and entrepreneurship to increase business performance that can be moderated by competitive advantage, which is focused on goodness of taste, for restaurants in Semarang. Based on pre – survey in 20 owners of restaurant, it can be concluded that there was decreasing income about 22% (Rp 335.000,00) and was followed by decreasing of market share about 0,56% during 3 months. It was interesting because the restaurants are one of SME that many people interested in it. In other hand, many people work in this sector as their main job.The samples of this research are the restaurants that include in SME, which employ 5 – 19 employees. This research used 150 respondents, but only 124 respondents who fulfill the requirement. The data were collected by using questionnaires and direct interviews to the owners of restaurants in Semarang. This research proves 5 (five) hypothesis that were built by capabilities organization, entrepreneurship, competitive advantage in goodness of taste, and business performance. The results was analyzed by AMOS. It can be concluded that the model is feasible. The results of this study indicate that the business performance can be increased directly by a good management of capabilities organization and indirectly can be reached by focusing to maintain the resources. It because the restaurants that include as SME have a limit resource.